Effect of Real-Time Surveys on Patient Satisfaction Scores in the Emergency Department. (1st April 2019) - Sobel, Julia; Bates, Jessica; Ng, Vivienne; Berkman, Matthew; Nuño, Tomas; Denninghoff, Kurt; Stoneking, Lisa
Abstract : Background . Patient satisfaction surveys have become increasingly important as their results help to determine Centers for Medicare and Medicaid Services (CMS) reimbursement. However, these questionnaires have known sources of bias (self-selection, responder, attribution, and nonresponse). Objective . We developed a real-time (RT) survey delivered in the hospital ED to evaluate the effect of implementing RT patient satisfaction surveys on physician behavior and hypothesized that the timing of patient satisfaction survey delivery would significantly impact the results. Method . Data from real-time patient satisfaction surveys were collected in phases from 12/2015 to 5/2017. Hospital-sponsored (HS) surveys were administered after discharge from 12/2015 to 12/2016. Results . For RT surveys, resident physicians were significantly more likely to write their names on the whiteboard (p = 0.02 ) and sit down (p = 0.01 ) with patients. Behavior modifications by attending physicians were not significant. Patient satisfaction measures did not improve significantly between periods for RT or HS surveys; however, RT survey responders were significantly more likely to recommend the ED to others. Conclusion . The timing of survey administration did significantly alter resident physician's behavior; however, it had no effect on patient satisfaction scores. RT responders were significantly more likely to recommend the emergency department to others.